Assessing the potential for restoring freshwater mussels to urban streams. Issue 3 (23rd November 2022) - Bukaveckas, Paul A.; Ryan, John‐Reid; Mair, Rachel
Abstract: Field trials were conducted to assess the potential for stocking native unionid mussels in urban streams of the Chesapeake Bay catchment. Juvenile, hatchery‐raised mussels were placed in enclosures at five urban streams (two restored and three unrestored) and two nearby rural streams. Adult mussels were translocated to two restored urban streams. Mussel growth and survivorship were assessed at the stream sites and for individuals maintained at hatchery ponds. At all sites, water quality conditions were generally suitable for mussels with respect to temperature, pH, and dissolved oxygen. Food resources, as indicated by the quantity and quality of suspended and benthic particulate matter, were higher among rural sites and lower in unrestored urban streams. Positive growth rates were observed at all sites, among both juveniles (caged) and translocated adults. Mussel fatty acid profiles were generally similar among sites, except for docosahexaenoic acid (DHA), which was lower among stocked mussels relative to mussels maintained at the hatchery. Among the unrestored urban streams, the frequent occurrence of high discharge events resulted in burial and downstream loss of enclosures. At restored urban streams and rural streams, the washout effects were less severe. Apart from washout effects, mortality, as indicated by the presence of dead mussels, was low (<10%). Overall, rural and restored urban streams provided suitable conditions for stocking native mussels, whereas in unrestored urban streams, bed and bank instability during high discharge events resulted in a high attrition of mussels. Conservation efforts may be aided by the consideration of mussel habitat needs in the design of stream restoration projects. The inclusion of mussel stocking efforts in urban stream restoration projects has the potential to facilitate stream recovery, expand and bring greater attention to mussel conservation efforts, and garner public support for the preservation of stream health in urban areas.